2014
DOI: 10.1097/prs.0000000000000361
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Nasoalveolar Molding Techniques in Unilateral Complete Cleft Lip Patients

Abstract: Therapeutic, II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 11 publications
1
52
0
Order By: Relevance
“…Nasal stenting has been used for maintenance of the alar cartilage form in clefts with stenosis. 25 - 28 Matsuo et al 29 demonstrated that the auricular cartilage could be molded with permanent results if the treatment was started within the first 6 weeks of life, due to the high degree of plasticity in the cartilage of infants during that period. They attributed this finding to the high levels of hyaluronic acid, which is a component of the proteoglycan aggregate of the intercellular matrix, in the cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…Nasal stenting has been used for maintenance of the alar cartilage form in clefts with stenosis. 25 - 28 Matsuo et al 29 demonstrated that the auricular cartilage could be molded with permanent results if the treatment was started within the first 6 weeks of life, due to the high degree of plasticity in the cartilage of infants during that period. They attributed this finding to the high levels of hyaluronic acid, which is a component of the proteoglycan aggregate of the intercellular matrix, in the cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…We did not segment the sutures of the viscero- and neurocranium as reported by others, 44 and we applied a force (0.7 N) that would result in mucogingival ulceration, if it was not corrected immediately. 49 Therefore, our results from the stress distribution patterns are expected to be higher than those in vivo. In particular, in the case of the scan of the newborn, a lower stress distribution can be expected, because such small structures (0.32 mm) as observed in the model are in reality supported by surrounding tissue, which would partially absorb or transmit the incoming load state.…”
Section: Discussionmentioning
confidence: 82%
“…Bennun and Figueroa [ 35 ] provided another modification known as dynamic presurgical nasal remodelling. Two of the selected studies assessed this last modified technique and both concluded that the Figueroa appliance (with a large nasal stent) decreases the risk of ulceration compared to the traditional (Grayson) appliance [ 58 , 59 ].…”
Section: Resultsmentioning
confidence: 99%